Determination of the optimal parameters and ionization products of riboxinum - Rosada, Mykola; Bevz, Nataliia; Georgiyants, Victoria (ScienceRise: Pharmaceutical Science, 2017)
Currently, mass spectrometry is one of the most widely used rapid methods of analysis; it is used to determine the structure of both individual synthetic and natural organic compounds and their mixtures. One of the ways to determine the structure of the compound studied by this method is the automatic comparison of the spectrum registered with the bank of spectra from the computer database. Aim. The aim of our work is to determine the optimal parameters of ionization and study the riboxinum fragmentation in ionization with the subsequent replenishment of the library spectra of the device. Methods. Mass spectrometry was applied using various systems to create both the parent and product ions with the subsequent use of the resulting data to improve selectivity and sensitivity of the method. Results. As a result of the research conducted the scheme of the riboxinum fragmentation in ionization on a mass spectrometer with a triple quadrupole has been studied. The optimal parameters of the riboxinum ionization have been determined. They are as follows: the ionization mode – positive; a drying gas – 15 L/min; a curtain gas – 8 L/min; the ionization voltage – 5000.0 kV; the temperature of a drying gas – 300.0 °С; the declustering potential – 40.0 V; the focusing potential – 200.0 V; the input potential at Q0 – 10.0 V; the collision energy (Q2) – 20.0 V; the output potential from the collision chamber (Q2) – 25.0 V. Conclusions. The results obtained are the basis for developing the method for the quantitative determination of riboxinum in biological samples by high-performance liquid chromatography with mass spectrometry-based detection